2010
DOI: 10.1007/s00253-010-2893-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community analysis of swine manure treated with autothermal thermophilic aerobic digestion

Abstract: Due to the environmental problems associated with disposal of livestock sludge, many stabilization studies emphasizing on the sludge volume reduction were performed. However, little is known about the microbial risk present in sludge and its stabilized products. This study microbiologically explored the effects of anaerobic lagoon fermentation (ALF) and autothermal thermophilic aerobic digestion (ATAD) on pathogen-related risk of raw swine manure by using culture-independent 16S rDNA cloning and sequencing met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Nevertheless, relatively little is known about the ATAD process compared with traditional treatments, including the activated-sludge process, composting process, and methane fermentation process (12). In particular, most reports focused on the analysis of bacterial community structures during the thermophilic phase of the ATAD process in either full-scale or lab-scale bioreactors (7,13,(15)(16)(17)(18)(19)(20). In this study, we dynamically monitored bacterial community structures from the mesophilic to thermophilic phases using a high-throughput sequencer with higher resolution than the PCR-DGGE method (6), and we elucidated the unique behaviors regarding the physicochemical parameters and bacterial community structures of the ATAD process for treating human excreta.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, relatively little is known about the ATAD process compared with traditional treatments, including the activated-sludge process, composting process, and methane fermentation process (12). In particular, most reports focused on the analysis of bacterial community structures during the thermophilic phase of the ATAD process in either full-scale or lab-scale bioreactors (7,13,(15)(16)(17)(18)(19)(20). In this study, we dynamically monitored bacterial community structures from the mesophilic to thermophilic phases using a high-throughput sequencer with higher resolution than the PCR-DGGE method (6), and we elucidated the unique behaviors regarding the physicochemical parameters and bacterial community structures of the ATAD process for treating human excreta.…”
Section: Discussionmentioning
confidence: 99%
“…Under mesophilic AD conditions, a T90 value of 1·8 days was obtained for E. rhusiopathiae, while at 53°C, the T90 value was reduced to 1–2 h. A study conducted by Han et al (2011) investigated the effects of an anaerobic lagoon fermentation and an autothermal thermophilic aerobic digestion on bacterial pathogens contained in raw swine manure. E. rhusiopathiae was present in the raw manure, however was no longer detectable following a mesophilic anaerobic lagoon fermentation.…”
Section: Treatment Methodsmentioning
confidence: 99%
“…Manure application loading rates are typically gauged by N concentration, leading to potential P runoff and eutrophication of water bodies in agricultural areas. The impacts of manure treatment processes before application should also be examined in relation to pathogen survival (Han et al, 2011) and the transformation and degradation of EDCs. Studies have shown that the contamination risk of manure‐derived heavy metals in cultivated plants varies with soil characteristics (Hao et al, 2008b; Li et al, 2009).…”
Section: Nps Pollutant Sources: Heavy Metals In Animal Manure Fertilizermentioning
confidence: 99%